Law, politics, and responding to injustice - Kirkby, Coel; Sadurski, Wojciech, 1950-; Walton, Kevin (Law teacher) (Abingdon, Oxon [UK] ; New York, NY : Routledge, 2025)
"This book examines the issue of injustice, and our responses to it, in a range of contemporary contexts. In her ground-breaking book The Faces of Injustice (1990), Judith Shklar draws attention to our tendency to view injustice as an abnormality. Of course it is not: injustice is ubiquitous. But how should we respond to it? The book brings together leading legal and political theorists to explore the nature of injustice, its relationship to law, and responses to it, in a variety of contexts. Their chapters cover issues such as protest, resistance, violence, the moral obligation to obey the law, civil disobedience, democratic reform, and transitional justice. They all, though, share a concern to examine such issues through a Shklar-inspired focus on injustice. This book will appeal to academics and advanced students in law, politics, and philosophy"--
Introduction / Coel Kirkby, Wojciech Sadurski, and Kevin Walton -- The Legal Experience of Injustice / David Dyzenhaus -- A Taxonomy of Injustice / Duncan Ivison -- Political Contempt, Divided Societies, and Transitional Justice / Colleen Murphy -- Finding Justice Between Accommodation and Refusal / Eddie Synot -- States of Injustice and Statuses of Legality / Nicole Roughan -- Bringing Heaven Down to Earth : Rights and Inclusion in Rawlsian Public Reason / Patrick Emerton and Jayani Nadarajalingam -- Beginning from Injustice / Ashwini Vasanthakumar -- Injustice and the Moral Obligation to Obey the Law / Jonathan Crowe -- Acting Together to Address Structural Injustice : A Deliberative Mini-Public Proposal / Ting-An Lin.
Keywords: Justice, Administration of -- Political aspects; Transitional justice; Justice (Philosophy); LAW / Jurisprudence; POLITICAL SCIENCE / History & Theory